Analisis Struktur dan Nilai Moral dalam Novel Si Bedog Panjang Karya Ki Umbara - Tita Rositawati; Leni Nuraeni (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2023)
The background of this research is that the researcher is interested in discussing and analyzing this novel, because no one has analyzed it structurally and morally. In addition, the novel Si Bedog Panjang written by Ki Umbara describes the daily life of a schoolboy which is suitable as a novel reading material. The purpose of this study is to find out the structure of the novel Si Bedog Panjang as well as the values contained in the novel Si Bedog Panjang by Ki Umbara. This research certainly uses descriptive methods. With literature study techniques as well as instruments in the form of data cards. The results of this study found that there are 3 moral values in the Novel Si Bedog Panjang, seen from the relationship between humans and themselves, there are 3 moral values in relationships with other humans, and also moral values towards the Creator there are 5.